Factors affecting the Use of Information by Visually Impaired Students: With Special reference to the Library, University of Colombo - Lankathilake, M.A.; Ramanan, T. (University Librarians Association, Sri Lanka, 2022)
Visually-impaired (VI) students still face unusual difficulties in accessing library resources although there are several assistive technologies and devices being available to help them to get access to information resources. Equality in services mandates libraries to strive for their best to assist these special-need users by examining and mitigating the challenges faced by them. In this regard, a case study was carried out at the Main Library of the University of Colombo, where 42 visually-impaired students were interviewed using a set of semi-structured interview questions. The study population constituted totally blind and partially impaired students. Issues facing by the respondents were identified over institutional, personal and technological factors. Out of different challenges they mentioned, lack of appropriate resources was drawing primary concern. Problems relevant to use of the Internet were identified based on 5 aspects: social, institutional, financial, personal, and technical issues. Those challenges significantly affected VI users having access to their learning resources. It was found that VI users were largely left out in the mainstream student community since they make up a very miniscule faction of the entire student population. Hence, it is recommended to establish a special assistance mechanism for VI users of the library, meanwhile training both VI students and library staff on finding information resources specifically intended for VI users, and using the assistive technologies and equipment.
Keywords: Braille books; Audio books; Visually-impaired users; Library